The Influence Of Price, Brand Image, And Product Quality On The Decision To Purchase A Viar Three-Wheel Motorcycle - Octavianeputri, Vicky; Abdullah, Zed; Pohan, Fanny Suzuda (Adpebi Science Series, 2024)
The purpose of this research is to determine the influence of the variables Price, Brand Image and Product Quality on the Purchase Decision of a Viar Three-Wheeled Commercial Motorbike in DKI Jakarta. This research uses quantitative methods. with a sample size of 100 respondents using purposive sampling technique . Data collection techniques through questionnaires. The data analysis used was SEM ( Structural Equation Modeling ) using smartPLS software. The research results show that the relationship between price and purchasing decision variables has a significant effect because it has a T statistic value of 3,484 > t table and a P value of 0.000 < 0.05. The original sample value of 0.357 indicates that the relationship between price and purchasing decisions is positive. Brand image has a significant influence on purchasing decisions because it has a T statistic value of 3,269 > t table and a P value of 0.001 < 0.05. The original sample value of 0.588 indicates that the price and purchasing decision is positive. Product quality has no significant influence on purchasing decisions because it has a T statistic value of 0.287 < t table and a P value of 0.774 > 0.05. The original sample value of 0.050 indicates that the direction of the relationship between product quality and purchasing decisions is positive .